Chapter Locality and the functional sequence in the left periphery - Rizzi, Luigi (De Gruyter, 2017)
This volume brings together a selection of articles illustrating the multifaceted nature of current research in generative syntax. The authors, including some of the leading figures in the field, present analyses of typologically diverse languages, with some studies drawing on dialectal, acquisitional and diachronic evidence. Set against this rich empirical background, the contributions address an equally wide range of theoretical issues.